Health-related quality of life in adults with hematological cancer: a 2023 cross-sectional survey from Qatar - Abdu, Yasamin; Ahmed, Khalid; Abdou, Mariam; Elhussein, Rayan; Sirelkhatim, Sayda; Bougmiza, Iheb; Yassin, Mohamed A.; Selim, Nagah A. (Frontiers in Oncology, 2024)
Background: Hematological cancers impose a complex burden on individuals, affecting their physical health and mental and emotional well-being. This study evaluated the health-related Quality of Life (HRQOL) and its determinants among adults with hematological cancers in Qatar in 2023.A cross-sectional study used a validated structured questionnaire conducted among adult patients diagnosed with hematological cancers. All adult patients who attended The National Centre for Cancer Care and Research (NCCCR) in Qatar during the Data collection period (January to March 2023) and agreed to participate were included in the study.Results: A total of 257 participants were enrolled in the study. The highest median (IQR) score of the HRQOL domain was observed in the functionating score of 90.6 (13.8), followed by the global health score of 83.3(25. 0). The median (IQR) of the symptoms burden score was 07.4(12.3). Gender significantly affects HRQOL, with males reporting better functioning and lower symptom burden than females. Employment status is positively associated with functioning scores. Regular exercise correlates with higher global health and functioning scores and lower symptom burden, while depressive symptoms are linked to poorer HRQOL outcomes. Patients experiencing cancer recurrence or active disease report lower global health and functioning scores and higher symptom burden. Treatment modalities such as chemotherapy and bone marrow transplant (BMT) timing also influence HRQOL, with recent treatment recipients showing lower global health and higher symptom burden scores. Depressive symptoms were the primary factor, lowering the global health score by 15.2%. Regarding the low functioning score predictors, female gender, depressive symptoms, and cancer recurrence emerged as significant predictors of the low functioning score. Furthermore, Regular exercise increased the functioning score by 03.4 units (p-value=0.018). Finally, Multiple linear regression analysis reinforced the significance of depressive symptoms, active disease status, and recurrence within the past five years as substantial predictors of higher symptom scores.The study emphasises the profound impact of depressive symptoms on all aspects of Health-Related Quality of Life (HRQOL), mainly affecting global health. It highlights the positive role of regular exercise in enhancing global health, functioning, and symptom burden scores.